The impact of the 1968 Prague spring on Czechoslovak and Yugoslav military doctrines - Torkar, Blaž (Acta Histriae, 2023)
This paper analyzes and compares the impact of the 1968 Prague Spring on military and strategic thinking in Czechoslovakia and Yugoslavia. A great change in the Czechoslovakian military caused Memorandum 68, a proposal of domestic military doctrine which consistently took into account the vital security interests of Czechoslovakia in international relations at that time. The document was mainly based on the inviolability of Czechoslovak territory and the right of its nations to defend their own existence regardless of the superpower interests of the Soviet Uni-on. At the same time Yugoslavia began to develop its own doctrine of the General People’s Defence and Social Self-Protection, which emphasized its total nature, creating the reality of the concept of a “nation in arms,” which attached great importance to soldiers and the art of soldiering in Yugoslavia.
Keywords: 20th century; Cecoslovacchia, Jugoslavia, Primavera di Praga, dottrina militare Memorandum 68, NATO, Patto di Varsavia; communism; Czechoslovakia; Češkoslovaška; Jugoslavija; Memorandum 68; Memorandum 68; military doctrine; NATO; People's Republic of Slovenia; Prague Spring; praška pomlad; Primorska region; sites of memory; Varšavski pakt; vojaška doktrina; Warsaw Pact; Yugoslavia